Telehealth-delivered naturalistic developmental behavioural intervention with and without caregiver acceptance and commitment therapy for autistic children and their caregivers: protocol for a multi-arm parallel group randomised clinical trial - Laurie McLay; Lisa Marie Emerson; Hannah Waddington; Jenna van Deurs; Jolene Hunter; Neville Blampied; Aaron Hapuku; Sonja Macfarlane; Nicholas Bowden; Lauren van Noorden; Mandy Rispoli (BMJ Open, 2023)
Introduction Timely access to early support that optimises autistic children’s development and their caregiver’s mental health is critical. Naturalistic developmental behavioural interventions (NDBIs) and acceptance and commitment therapy (ACT) are evidence-based supports that can enhance child learning and behaviour, and adult well-being, respectively. The traditional face-to-face delivery of these approaches is resource intensive. Further, little is known about the benefit of parallel child-focused and caregiver-focused supports. The aims of this trial are to evaluate the effectiveness and social validity of telehealth-delivered, caregiver-implemented, child-focused NDBI and caregiver-focused ACT when delivered alone and in parallel, on autistic children’s social communication and caregiver well-being.Methods and analysis The study will use a randomised, single-blind clinical trial with three parallel arms: NDBI; ACT and ACT+NDBI. We will recruit a minimum of 78, 2–5-year-old autistic children and their families throughout Aotearoa New Zealand. Support will be delivered over 13 weeks using a combination of culturally enhanced web-based modules and online group coaching. Primary outcome variables include children’s social communication/engagement with their caregiver as well as caregiver stress and will be evaluated using a repeated measures multivariate analysis of variance. Outcome variables are assessed at baseline (before randomisation), immediately postparticipation and at 3-month follow-up.Ethics and dissemination The trial is approved by the Health and Disability Ethics Committee (2022 FULL 12058). The findings of this trial will be disseminated through peer-reviewed journals and national and international conference proceedings regardless of the magnitude/direction of effect. Additionally, data will be shared with stakeholder groups, service providers and health professionals.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12622001134718).